THE INFLUENCE OF SLOW STEAMING ON FUEL USAGE AND CARBON EMISSIONS OF CONTAINER SHIPS: A CASE STUDY OF THE SURABAYA-MAKASSAR ROUTE - SW Meiliana; H Syahab; AI Wulandari; IKAP Utama (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2024)
The practice of slow steaming in maritime transport, initially introduced in the 1970s during the first oil crisis, has evolved into a strategy offering both cost reduction and environmental benefits. The overall combined costs for carriers and shippers experienced significant reductions with slow steaming, with extra slow steaming yielding even greater cost savings. While slow steaming is not the sole method to reduce fuel consumption and emissions, it proves to be the most efficient in terms of time and cost. Shipping operators globally recognize its advantages, as it aligns with environmental sustainability efforts by reducing greenhouse gas emissions. This study carried out a comprehensive exploration of the effects of slow steaming on container ships, focusing specifically on the Surabaya-Makassar route. The research aims to learn how much the impact of slow steaming on the ship operation. This study analyzes the impact of slow steaming on container ships in terms of fuel consumption and carbon emissions on the Surabaya-Makassar route. The lowest speed is 5 knots, and the highest speed is 11 knots. At a speed of 5 knots, fuel consumption decreases by 5% compared to the ship's speed at 11 knots. The same applies to the reduction in carbon emissions.